The 3 June 1944 tragedy of Pirčiupiai village: historiography and sources - Zizas, Rimantas (Genocidas ir rezistencija, 2025)
Pirčiupiai – a village in southeastern Lithuania (Dzūkija), which has entered the history of Lithuania by the fact that on 3 June 1944 German executioners carried out an extremely cruel mass terror action, burnt down the main part of the village of Pirčiupiai – Naujieji Pirčiupiai, massacred the people of the village, burnt them alive or shot them. According to the version of events, which was already established in 1944 and unchanged in the historiography, a total of 119 people were murdered, 61 women and 58 men. The article reviews the historiography of the Pirčiupiai tragedy and the most important archival sources, with the aim of revealing how the events of the village tragedy have been covered over a period of 80 years, and how the narrative of this story has been shaped. It raises the question of the relationship of the rural people to the Soviet partisans, their participation in Soviet partisan activities and other issues as factors that could have contributed to the tragedy of the village, which the Soviet historiography tried to keep silent? The article addresses and attempts to answer the question of what circumstances led to the exceptional brutality of the German executioners, and presents archival evidence that the German losses in the ambush on the morning of 3 June 1944 near Pirčiupiai may have been higher than those reported in Soviet historiography. It is noted that the story of the village tragedy was politicised and used for propaganda purposes: the authors of Soviet historiography unsuccessfully searched for traces of the involvement of Lithuanian “bourgeois nationalists” in the execution of the Pirčiupiai. In response to the Soviet narrative of the Pirčiupiai tragedy, the diaspora authors used counter propaganda measures - they viewed the Soviet partisans and the repressive structures of the NKVD-NKGB as the perpetrators of the massacre of the village, and they raised questions of their moral responsibility. The article attempts to look at how the events of the Pirčiupiai tragedy were reflected in the restricted archival sources of Lithuania during the Soviet period, how they were accumulated, what they are, and what is the history of their appearance.